On Dec 8, 9:36 pm, robin hankin <hankin.ro...@gmail.com> wrote: > hello > > I have been playing with assumptions(). I want to assume a>b > but solve() gives me a solution which is not consistent with this: > > sage: var('a b') > (a, b) > sage: assume(a>b) > sage: assumptions() > [a > b] > sage: solve([a+b==2,a-b==0],a,b) > [[a == 1, b == 1]] > sage: > > How come the solution (viz a=b=1) is not consistent with my assumption()? > > -- > Robin Hankin > Uncertainty Analyst > hankin.ro...@gmail.com
Sometimes one can use workarounds: sage: var('a b') (a, b) sage: sol=solve([a+b==2,a-b==0],a,b) sage: [s for s in sol if s[0].rhs()>s[1].rhs()] [] sage: sol=((x+1)*x*(x-1)==0).solve(x) sage: [s for s in sol if s.rhs()>0] [x == 1] sage: var('x y') sage: sol=solve([x^2-4*x+y^2==0,y^4==x^2],x,y) sage: [s for s in sol if all([s[0].rhs()>0,s[1].rhs()>0])] [[x == 3, y == sqrt(3)]] -- To post to this group, send email to sage-support@googlegroups.com To unsubscribe from this group, send email to sage-support+unsubscr...@googlegroups.com For more options, visit this group at http://groups.google.com/group/sage-support URL: http://www.sagemath.org